Creative Entrepreneurship Training in Product Creation at SMA RK 2 Kabanjahe: Pelatihan Kewirausahaan Kreatif dalam membuat Produk di SMA RK 2 Kabanjahe - Gaul, Mariani Meri Lumban; Waruwu, Ermina; Fajariyanto, Tri Chandra; Gurusinga, Rikha Emmya; Logo, Natanael Nilikmo; Lumban Gaol, Rina Martasari (Universitas Lancang Kuning, 2024)
This community service activity aimed to enhance the entrepreneurial skills of students at SMA RK 2 Kabanjahe by providing training in the production of fabric softeners and dishwashing liquid. The project-based learning (PBL) method allowed students to be directly involved in every phase of the production process, from planning to evaluation. A total of 100 students from grades X, XI, and XII participated in this activity, with an implementation method that included planning, preparation, execution, practice, and evaluation. The results of the pre-test and post-test showed significant improvements in students' knowledge and skills. Knowledge about dishwashing liquid increased by 60%, knowledge about fabric softeners by 67%, and practical skills increased by 112%. Although the production process went well, there were issues related to time management, marketing, and product distribution. To maximize students' ability to run their businesses, additional training in business management and marketing strategies is needed. Overall, this activity successfully fostered students' initiative and practical skills.